Effect of Digoxin Therapy on Mortality in Patients With Atrial Fibrillation: An Updated Meta-Analysis - Wang, Xiaoxu; Luo, Yi; Xu, Dan; Zhao, Kun (Frontiers in Cardiovascular Medicine, 2021)
Background: Whether digoxin is associated with increased mortality and a reduction in readmission for atrial fibrillation (AF) remains controversial. We aimed to assess the clinical effects of digoxin in patients with AF. Methods: PubMed, EMBASE, and the Cochrane library were systematically searched to identify eligible studies comparing the outcomes of patients with AF taking digoxin with those not taking digoxin. Adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) were extracted and pooled. Results: A total of 29 studies with 621,478 patients were included. Digoxin use was associated with an increased risk of all-cause mortality in all patients with AF (HR 1.17, 95% CI 1.13–1.22, P < 0.001), especially in patients without heart failure (HF) (HR 1.28, 95% CI 1.11–1.47, P < 0.001). There was no significant association between digoxin and mortality in patients with AF and HF (HR 1.06, 95% CI 0.99–1.14, P = 0.110). In all patients with AF, regardless of concomitant HF, digoxin use was associated with an increased risk of sudden cardiac death (SCD) (HR 1.40, 95% CI 1.23–1.60, P < 0.001) and cardiovascular mortality (HR 1.27, 95% CI 1.08–1.50, P < 0.001), but digoxin use had no significant association with all-cause hospitalization (HR 1.13, 95% CI 0.92–1.39, P = 0.230). Conclusion: We conclude that digoxin use is associated with an increased risk of all-cause mortality, cardiovascular mortality, and SCD, but it does not reduce readmission for AF, regardless of concomitant HF. Digoxin has a neutral effect on all-cause mortality in patients with AF with concomitant HF.